2022
DOI: 10.1002/acn3.51708
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of glial fibrillary acidic protein in patients with amyotrophic lateral sclerosis

Abstract: Objective To compare serum levels of the astrocyte biomarker glial fibrillary acidic protein (GFAP) in patients with amyotrophic lateral sclerosis (ALS) and neurologically healthy controls and to analyze the relations between serum GFAP (sGFAP) and phenotype in ALS. Methods We studied 114 ALS patients and 38 controls. sGFAP was quantified with single molecule array (Simoa) technology. Results In both ALS patients and controls, sGFAP moderatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 64 publications
2
3
1
Order By: Relevance
“…One of the clearest findings of our study is the lack of association of sNFL levels with cognitive deficits in ALS. The apparent independence of sNFL from extra-motor pathology contrasts with the recent report of higher serum GFAP levels in ALS patients with neuropsychological abnormalities ( Falzone et al, 2022 ; Verde et al, 2023 ). The motor specificity of NFL might be a consequence of the unique amount of NFL which the axon of a degenerating MN, given its length, can release.…”
Section: Discussioncontrasting
confidence: 89%
“…One of the clearest findings of our study is the lack of association of sNFL levels with cognitive deficits in ALS. The apparent independence of sNFL from extra-motor pathology contrasts with the recent report of higher serum GFAP levels in ALS patients with neuropsychological abnormalities ( Falzone et al, 2022 ; Verde et al, 2023 ). The motor specificity of NFL might be a consequence of the unique amount of NFL which the axon of a degenerating MN, given its length, can release.…”
Section: Discussioncontrasting
confidence: 89%
“…Similarly, we found no differences in plasma levels across onset types and clinical phenotypes. Taken together, these data, in agreement with previous reports in smaller ALS cohorts [ 18 , 19 ], suggest that plasma GFAP elevation in ALS also reflects the astrocytic activation secondary to neurodegeneration at sites unrelated to motor neurons. The moderate association between plasma GFAP and parameters of cognitive impairment, including ALS-specific ECAS scores, the BMDB total score, and the scores in tests exploring semantic fluency and constructional praxis, suggest a link with extra-motor cortical areas.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the possible influence of gender on plasma GFAP values, we found that in our ALS population females showed higher biomarker levels than males, with the difference almost reaching statistical significance. Higher plasma GFAP values in females were previously reported in ALS patients, albeit potentially related to the older age [ 19 ], and in subjects with other neurodegenerative disorders as well [ 12 , 13 ]. However, such a difference was not highlighted in other patient groups [ 22 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…complications due to frontotemporal dementia or cognitive impairmen. 53 , 54 In addition, neurofilament light chain (NfL), one of the polypeptide chains of the neurofilament triplet that structurally supports the neuronal cytoskeleton of axons, was shown to be a suitable diagnostic marker and strongest predictor of patient survival. 51 , 52 , 54 Ubiquitin C-terminal hydrolase UCHL1 was established as a robust prognostic indicator for stratifying slow disease progression and survival rates in patients with low levels of neurofilament light chain.…”
Section: Discussionmentioning
confidence: 99%